Responses of pig embryos to amino acids - C F Rosenkrans; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1988)
Mixtures of vitamins and amino acids produced detrimental effects on the development of pig embryos. However, addition of three amino acids, phenylalanine, methionine, and isoleuncine, enhanced pig embryo development.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Embryo survival; Pregnancy; Amino acids